Legal Consequences of Not Applying the Prudential Principle in the Sale and Purchase Agreement by the Land Deed Official - Fira Fairima Fiorentina (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The Land Deed Official as the official authorized to issue the Authentic Deed is obliged to examine the truth of the documents that are a requirement in the issuance of the Notarial Sale and Purchase Agreement. In practice, there are Land Deed Officials who ignore the obligation to examine the documents brought by the parties as in the case of Muslims in Decision Number 538/Pid.B/2019/ PN.Pdg where there is a forgery of signatures by the parties in the agreement to make a Notarial Sale and Purchase Agreement, the testimony of the reporting witness which was later corroborated by the results of the criminalistics laboratory examination showed that the signature in the Notarial Sale and Purchase Agreement was declared non-identical to the actual signature, as a result, the Notarial Sale and Purchase Agreement caused losses to other parties. Notarial Sale and Purchase AgreementNotarial Sale and Purchase Agreement Based on these problems, it raises the question of what are the legal consequences of not applying the prudential principle in the Notarial Sale and Purchase Agreement by the Land Deed Official and what are the legal consequences of the validity of the Notarial Sale and Purchase Agreement which is proven to have forged signatures in the deed. The research method used is normative juridical research using a statutory approach and a case approach using data collection methods through documentation studies and literature studies of court decisions. The result of the research is that a Land Deed Official who does not apply the principle of prudence can be subject to administrative sanctions following the mistakes made, as for the validity of the Notarial Sale and Purchase Agreement which is proven to have a forged signature, the Notarial Sale and Purchase Agreement is declared null and void. A Land Deed Official in making an authentic deed must pay attention to the prudential principle, one of which is by requiring the parties to be present in person and checking the authenticity of the parties' identities to prevent identity forgery in making a Notarial Sale and Purchase Agreement. prudentialNotarial Sale and Purchase AgreementNotarial Sale and Purchase Agreement Keywords: Prudential Principle; Notarial Sale and Purchase Agreement; Land Deed Official; Forgery of Signature.Notarial Sale and Purchase Agreement